Bronchiolitis in an infant due to influenza A, necropsy findings: a case report - dos Santos Souza, Daniela Cristina; Mussatto, Diego Henrique Ferreira; Costa, Paula de Almeida Souza Santos da; Menezes, Ellen Diniz de; Zanelatto, Magno Giovani; Moraes, Marcelo Padovani de Toledo; Domingues, Maria Aparecida Custodio; Oliveira, Pedro Marciano de; Terra, Simone Antunes; Ojopi, Elida Paula Benquique (Brazilian Journal of Case Reports, 2024)
The influenza virus is an important cause of respiratory disease in infants and presents challenging differential diagnoses to investigate. This is a case report that involves a necroscopic study of a 2-month-old male infant, without previous comorbidities, with a serological diagnosis of influenza A and histopathological presentation of non-obliterating bronchiolitis. Infants are considered a high-risk group for flu complications due to the immaturity of the immune system and the ability to respond to respiratory infections. Furthermore, the severity of infection in infants may be worsened by the difficulty in quickly considering and treating the symptoms of the disease.